Mengatasi Stunting Dengan Menggunakan Sosialisasi dan Demo Masak Pada Wilayah Nagari Palaluar - Amalia Kartika Yani (STAI Al-Amin Gersik Kediri Lombok Barat-NTB, 2025)
Stunting, or known as short toddlers, is a condition where children under five experience stunted growth due to chronic malnutrition, causing their height to be lower than children their age. Real Work Lectures (KKN) is an extracurricular program that provides real work experience to students in the community. The UNP KKN team implemented the program in Nagari Palaluar, Sijunjung Regency, West Sumatra, which has a significant stunting problem. Based on data from the Tanjung Ampalu Community Health Center, it was found that 39 toddlers were stunted in Nagari Palaluar. This KKN program includes outreach about the dangers of stunting and how to prevent it, as well as cooking demonstrations to show how to cook nutritious food. The results show that this method is effective in increasing public awareness and knowledge about stunting.